Two research methods for studying sexual diversity at school: ethnography and case study (Itinerarios Educativos, 2021)
This article discusses and reflects on the methods selected for the development of a qualitative research work that explores school conflicts that affect sexual diversity. Four middle schools of Santa Fe, Argentina, become the scenario for grasping teachers and students’ − belonging or not to LGBT+ communities − perceptions of sexuality. First, research objectives and the case study method are presented. The case is addressed as a system with constraints (Stake, 1995). This method is so versatile that enables a simultaneous analysis considering multiple overlapping social aspects (Yin, 1989), which is highly convenient for school observations. Second, our work poses a reflection on the potentialities of ethnography to strengthen methodological design. During field work development, the researcher’s personal life story at school − determined by his sexual orientation − can act as both a motivation and a constraint. For that reason, two meanings of ethnography proposed by Rosana Guber (2001) (ethnography as an approach and as a method) were included with particular emphasis on the importance of the notion of reflexivity for field work development.
Keywords: sexual diversity; school; case study; ethnography